P074 Night-to-night variability in obstructive sleep apnoea severity is associated with hypertension and high misdiagnosis rates. (7th October 2021) - Lechat, B; Naik, G; Reynolds, A; Aishah, A; Scott, H; Loffler, K; Vakulin, A; McEvoy, R; Adams, R; Catcheside, P; Eckert, D
Abstract: Introduction: The impact of night-to-night variability in obstructive sleep apnoea (OSA) severity on important health outcomes such as blood pressure is unknown. This study aimed to determine the effects of night-to-night variability in the apnoea/hypopnoea index (AHI) on hypertension risk and OSA misdiagnoses. Methods: In-home nightly monitoring of 67, 278 participants from 151 countries, over ~170 nights per participant between July 2020 to March 2021 using a validated under mattress sleep analyser. Blood pressure measurements were available in 12, 295 participants. OSA was defined as a mean nightly AHI >15events/h. Night-to-night variability was assessed as the standard deviation of AHI across nights. Results: 22.6% (95% CI: 20.9–24.3) of the cohort (13% of women, 25% of men) had an average AHI> 15 events/h sleep. The average nightly AHI variability ranged from 3±1 in people without OSA to 14±6 in people with severe OSA. Higher mean AHI (OR [95% CI], 1.44 [1.29, 1.61]) and greater nightly variability in AHI (1.57 [1.39, 1.76]) were associated with hypertension. In people with a mean AHI of ≥5 events/h, high night-to-night AHI variability was associated with a ~30% increased risk in hypertension, independent of OSA severity category. Likelihood of misdiagnosis of OSA based on a single night compared to the mean across all nights was ~20%; this decreased with more monitoring nights. Conclusions: These findings highlight the novel, important information that simple multi-night monitoring of OSA can yield. This includes the potential importance of night-to-night variation and its contribution to hypertension and increased confidence of OSA diagnoses.